i-CR (i-class replacement) - Muhamad, Sarah Anissa (Universiti Teknologi MARA, Kedah, 2019)
In order to have a class replacement, lecturer of UiTM Johor, Kampus Segamat need to go to the HEA’ department and fill up the form. If there is any typo error, they need to fill up a new form as a form with a typo error will be charged as invalid to HEA (Hal Ehwal Akademik). Not just that, it has a high tendency to lose or misplaced the form that has been submitted by the applicants. These kinds of situation will only cause a burden to the lecturer as they need to fill up all the data again. Objective of this system is to expedite the process of having an approval from both department which is HEA and KPP (Ketua Pusat Pengajian) besides to save cost of university in spending cost on paper to print the correspondence. HEA’ department which is the responsible person to print the official correspondence can cut the cost in printing it. This is because, lecturer that apply the class replacement will receive and can check a correspondence with approval from both department through i-CR. i-CR is a new system that is being developed as to make easy for its users in replacing a class. Plus, this system can be use anytime and anywhere that the users want as i-CR is being online. This system can be commercialized for other university and college also as it is not only for UiTM Johor. In terms of functionality, i-CR is not limited to apply a class replacement only but also can generate a correspondence that have been approve by HEA and KPP.